2017
DOI: 10.1002/ece3.3608
|View full text |Cite
|
Sign up to set email alerts
|

Do invasive plants structure microbial communities to accelerate decomposition in intermountain grasslands?

Abstract: Invasive plants are often associated with greater productivity and soil nutrient availabilities, but whether invasive plants with dissimilar traits change decomposer communities and decomposition rates in consistent ways is little known. We compared decomposition rates and the fungal and bacterial communities associated with the litter of three problematic invaders in intermountain grasslands; cheatgrass (Bromus tectorum), spotted knapweed (Centaurea stoebe) and leafy spurge (Euphorbia esula), as well as the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 55 publications
0
6
1
Order By: Relevance
“…The downtrend in CO 2 evolution rates did not mean that microbes would die or activity decline in a short time (Li et al, 2015), and this was further confirmed by the PLFA data (Table 3). Previous studies suggested that the increasing easily-available matter (especially labile C) would accelerate the turnover of microorganisms (rstrategists, mainly bacteria) in the early phase, and later replaced by k-strategists (mainly fungi) due to growth-limiting substrate concentrations (Fontaine et al, 2003;Dilly et al, 2004;McTee et al, 2017), however, our bacteria and fungi biomass data did not show this trend during decomposition process.…”
Section: Discussioncontrasting
confidence: 84%
“…The downtrend in CO 2 evolution rates did not mean that microbes would die or activity decline in a short time (Li et al, 2015), and this was further confirmed by the PLFA data (Table 3). Previous studies suggested that the increasing easily-available matter (especially labile C) would accelerate the turnover of microorganisms (rstrategists, mainly bacteria) in the early phase, and later replaced by k-strategists (mainly fungi) due to growth-limiting substrate concentrations (Fontaine et al, 2003;Dilly et al, 2004;McTee et al, 2017), however, our bacteria and fungi biomass data did not show this trend during decomposition process.…”
Section: Discussioncontrasting
confidence: 84%
“…Our findings are in line with previous work showing that the addition of organic amendments in agricultural soils can affect fungal biomass and community compositions in soils (Clocchiatti et al, 2020;Moll et al, 2015;Reardon & Wuest, 2016) and that leaf litters (Asplund et al, 2018;Keiser et al, 2011;Lin et al, 2019;Veen, Snoek, et al, 2019) and decomposing wood (Purahong et al, 2019) are associated with unique microbiomes on their surface. We now progress on this understanding and show that repeated additions of a certain organic input can result in the development of litter-specific soil fungal communities (Fanin et al, 2014;McTee et al, 2017). In our approach we used sterilised litter in order to prevent the introduction of 'home' decomposers from the phyllosphere with the litter itself and focused on how interactions between soil and litter type affected litter mass loss and the microbes present in the soil.…”
Section: Directional Shifts In Soil Microbial Community Compositionmentioning
confidence: 99%
“…climate change, land use change disturbance; Landhäusser et al., 2010) undoubtedly alter ecosystem processes and function, including soil microbial community structure (Kourtev et al., 2002; Stefanowicz et al., 2016) and soil C and nutrient cycling associated with litter decomposition (Ashton et al., 2005; Liao et al., 2008). However, the linkage between microbial community structure and litter decomposition in the context of plant community change is still less understood (Arthur et al., 2012; Kourtev et al., 2002; McTee et al., 2017). Emerging evidences show that microbial community structure may adapt to nutrient condition/limitation, for example, nitrogen (N) and phosphorous (P), to control the litter decomposition (Hoyos‐Santillan et al., 2018; Kaiser et al., 2014), which hints a feedback between decomposition and microbial composition when plant community changes, but field evidence remains lacking.…”
Section: Introductionmentioning
confidence: 99%